2015
DOI: 10.1002/smi.2622
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Racial Discrimination and Ambulatory Blood Pressure in Women with Type 2 Diabetes

Abstract: Diabetes is the only disorder in which women's risk for heart disease exceeds men's. Elevated blood pressure (BP) increases cardiovascular risk in people with type 2 diabetes. Racial discrimination and neuroticism are both associated with BP levels but have not been examined in concert. This study investigated self-reported racial discrimination, neuroticism and ambulatory BP in women with type 2 diabetes. Thirty-nine Black and 38 White women completed a race-neutral version of the Schedule of Racist Events; B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Dietary information was not collected in the MIDUS study, which may be an important confounding or mediating variable in the association between perceived weight discrimination and allostatic load—particularly because poor dietary choices have been related to the effects of discrimination on glycemic control [46]. Participant non-response rates on the questions about perceived discrimination also reduced the final sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary information was not collected in the MIDUS study, which may be an important confounding or mediating variable in the association between perceived weight discrimination and allostatic load—particularly because poor dietary choices have been related to the effects of discrimination on glycemic control [46]. Participant non-response rates on the questions about perceived discrimination also reduced the final sample size.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study that provides information from the same population of patients with type 2 diabetes on physical health, mental health and self-care behaviors. Previous work in diabetes has focused on the relationship between psychological distress, mental health, and physical outcomes [15,18]; however, little research has investigated the impact of perceived discrimination on health behaviors. These results suggest that while a direct association to physical health outcomes may not exist, perceived discrimination has an influence on the mental component of quality of life and health behaviors, and thus should be addressed through educational programs focused on improving health in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, while there was a significant association with MCS, perceived discrimination did not have an impact on biologic measures other than blood pressure in African Americans. Previous research found significant associations with mean continuous glucose, insulin resistance, and glycemic control [15,18], however, these studies were only conducted in women and sample sizes were much smaller. This study found that while a significant association with physical health outcomes was not present, health behaviors were associated with perceived discrimination and may be an appropriate way to mitigate the impact of perceived discrimination on health outcomes in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Discrimination in daily life has been documented to negatively influence well-being 12 and glycemic control, 13,14 partially mediated through psychological distress. 15,16 Research has found a negative relationship between discrimination and an array of health outcomes.…”
Section: Introductionmentioning
confidence: 99%